Immune responses after fractional doses of inactivated poliovirus vaccine using newly developed intradermal jet injectors: A randomized controlled trial in Cuba. Issue 2 (3rd January 2015) - Resik, Sonia; Tejeda, Alina; Mach, Ondrej; Fonseca, Magile; Diaz, Manuel; Alemany, Nilda; Garcia, Gloria; Hung, Lai Heng; Martinez, Yenisleydis; Sutter, Roland
Abstract Introduction The World Health Organization recommends that, as part of the new polio endgame, a dose of inactivated poliovirus vaccine (IPV) be introduced by the end of 2015 in all countries using only oral poliovirus vaccine (OPV). Administration of fractional dose (1/5th of full dose) IPV (fIPV) intradermally may reduce costs, but its administration is cumbersome with BCG needle and syringe. We evaluated performance of two newly developed intradermal-only jet injectors and compared the immune response induced by fIPV with that induced by full-dose IPV. Methods Children between 12 and 20 months of age, who had previously received two doses of OPV, were enrolled in Camaguey, Cuba. Subjects received a single dose of IPV (either full-dose IPV intramuscularly with needle and syringe or fIPV intradermally administered with one of two new injectors or with BCG needle or a conventional needle-free injector). Serum was tested for presence of poliovirus neutralizing antibodies on day 0 (pre-IPV) and on days 3, 7 and 21 (post-vaccination). Results Complete data were available from 74.2% (728/981) subjects. Baseline median antibody titers were 713, 284, and 113 for poliovirus types 1, 2, and 3, respectively. Seroprevalence at study end were similar across the intervention groups (≥94.8%). The immune response induced with one new injector was similar to BCG needle and to the conventional injector; and superior to the other new injector. fIPV induced significantly lower boosting response compared to full-dose IPV. No safety concerns were identified. Interpretation One of the two new injectors demonstrated its ability to streamline intradermal fIPV administration, however, further investigations are needed to assess the potential contribution of fIPV in the polio endgame plan.